Theoretical fundamentals of information presentation and processing using potential codes - Bykov, M. M.; Konate, K.; Raimi, A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Theoretical fundamentals of generalized method of knowledge representation about objects of external world by rank transformation of their descriptions, performed in different parametric spaces — deterministic, probabilistic, fuzzy and others, as well as models of rank configurations are suggested. The method of the rank configuration description by the DRP — code (distance rank storing code) is developed. The problems of its completeness, information capacity, noise immunity and secrecy are considered.